2014
DOI: 10.1111/eva.12134
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of an invasive shrub affects tolerance and resistance to defoliation by a biological control agent

Abstract: Evolution has contributed to the successful invasion of exotic plant species in their introduced ranges, but how evolution affects particular control strategies is still under evaluation. For instance, classical biological control, a common strategy involving the utilization of highly specific natural enemies to control exotic pests, may be negatively affected by host hybridization because of shifts in plant traits, such as root allocation or chemical constituents. We investigated introgression between two par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 80 publications
(208 reference statements)
1
35
0
Order By: Relevance
“…Likewise, the date of leaf senescence was correlated with latitude for both Tamarix and P. deltoides genotypes in the common garden (Friedman et al ., 2011). Studies have also shown that northern populations of Tamarix have a larger root to shoot ratio, indicating that northern populations allocate more biomass to belowground tissues than southern populations (Sexton et al ., 2002; Williams et al ., 2014). For populations experiencing higher rates of freeze-induced dieback, it may be adaptive to have larger pools of carbon in the form of belowground biomass for replacement growth of dead tissues when the growing season resumes.…”
Section: Evidence For Local Adaptation In Tamarix Common Garden Studiesmentioning
confidence: 99%
“…Likewise, the date of leaf senescence was correlated with latitude for both Tamarix and P. deltoides genotypes in the common garden (Friedman et al ., 2011). Studies have also shown that northern populations of Tamarix have a larger root to shoot ratio, indicating that northern populations allocate more biomass to belowground tissues than southern populations (Sexton et al ., 2002; Williams et al ., 2014). For populations experiencing higher rates of freeze-induced dieback, it may be adaptive to have larger pools of carbon in the form of belowground biomass for replacement growth of dead tissues when the growing season resumes.…”
Section: Evidence For Local Adaptation In Tamarix Common Garden Studiesmentioning
confidence: 99%
“…An increased genetic potential in hybrid populations may facilitate subsequent colonization and establishment, and allow genetically admixed individuals to tap into novel niches within the invaded range not typically occupied by any of its ancestors (Lockwood et al 2007;Yoder et al 2010;Williams et al 2014). For hybrids to persist, however, their distribution (in allopatry) and/or the balance between selection and gene flow (in sympatry or parapatry) should help establish reproductive isolation (Grant 1994;Buerkle et al 2000;Mallet 2007;Nolte & Tautz 2010;Abbott et al 2013;Seehausen et al 2014).…”
Section: Accepted Articlementioning
confidence: 99%
“…Thus, theoretical considerations notwithstanding, there is a need to identify systems appropriate for the study of the incipient stages of hybrid lineage formation and subsequent speciation (Buerkle et al 2000;Nolte & Tautz 2010;Seehausen et al 2014). The identification of newly formed hybrid lineages can not only provide key insights into the formation of new hybrid species, but also answer important questions related to the pace of hybrid lineage stabilization and the associated extent of genomic integration (Nolte & Tautz 2010;Abbott et al 2013;Seehausen et al 2014;Williams et al 2014). …”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Friedman et al [47] and Gaskin and Kazmer [29] found that the F1, F2, and backcrosses to two parent species, T. ramosissima and T. chinensis, may represent 83-87% of the tamarisk invasion in the western United States. Recent studies have found that this complicates the biological control of the genus, because increased levels of T. ramosissima introgression resulted in higher investment in roots and tolerance to defoliation, and less resistance to biological control agents often used by managers to decrease the range and spread of this genus [48]. Plant hybridization, particularly in this harmful invasive species, may hinder containment efforts in natural areas.…”
Section: Conservation Concerns Of Hybrid Swarmsmentioning
confidence: 99%